Maqashid Sharia Assessment of Gold Installment Financing Among Bank Syariah Indonesia (BSI) Customer’s - Rahmawati; Mustaming; Takdir; Darmawati Hanafi; San Syafakillah (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose  – This research aims to examine the customers’ perceptions of gold installment financing service at BSI Palopo by using an ethical framework of maqāṣid al-sharī‘ah, which apply in Islamic banking. The study also provides a legal analysis of the contractual structure (akad), ownership issues (milk), and Shariah compliance concerning gharar, riba, and risk, as required by the journal's focus. The study has discussed on how the Islamic higher objectives of wealth and customer purification, Sharia compliance are met through gold installment financing. Method – The approach used was qualitative descriptive with customers of Bank Syariah Indonesia (BSI) using the Cicil Emas financing product as participants, Data were collected trough semi- structured interview and nd transcribed verbatimThe analysis was informed by the five maqāṣid categories namely, protection of religion, well-being, intellect, wealth and posterity Result – It is found that in general customers consider gold installment financing as religiously acceptable modus operandi which help them to stay away from riba through fixed price item and offer financial stability by manageable installments. Ḥifẓ al-māl appeared as the strictest mqaasid-based output regarding gold, considered a safe investment over the long term, allowing disciplined savings and future-oriented projects. But with low knowledge of contract instruments and fear of delayed ownership, ethical issues arise in terms of transparency and potential ambiguity.These results indicate that gold installment financing is a major product innovation in maqāṣid-based IF and call for greater customer education, improved disclosure standards, and welfare-focused product governance. Implication – This study suggests that gold installment financing is congruent with maqāṣid al-sharī‘ah, especially wealth protection and prevention of riba. Nonetheless, partial customer awareness emphasizes the importance of financial literacy, transparent disclosure and robust maqāṣid-based